Chlorophyll Synthesis in Dark-Grown Pine Primary Needles - Schoefs, Benoît (American Society of Plant Physiologists, 1998)
The pigment content of dark-grown primary needles of Pinus jeffreyi L. and Pinus sylvestris L. was determined by high-performance liquid chromatography. The state of protochlorophyllide a and of chlorophylls during dark growth were analyzed by in situ 77 K fluorescence spectroscopy. Both measurements unambiguously demonstrated that pine primary needles are able to synthesize chlorophyll in the dark. Norflurazon strongly inhibited both carotenoid and chlorophyll synthesis. Needles of plants treated with this inhibitor had low chlorophyll content, contained only traces of xanthophylls, and accumulated carotenoid precursors. The first form of chlorophyll detected in young pine needles grown in darkness had an emission maximum at 678 nm. Chlorophyll-protein complexes with in situ spectroscopic properties similar to those of fully green needles (685, 695, and 735 nm) later accumulated in untreated plants, whereas in norflurazon-treated plants the photosystem I emission at 735 nm was completely lacking. To better characterize the light-dependent chlorophyll biosynthetic pathway in pine needles, the 77 K fluorescence properties of in situ protochlorophyllide a spectral forms were studied. Photoactive and nonphotoactive protochlorophyllide a forms with emission properties similar to those reported for dark-grown angiosperms were found, but excitation spectra were substantially red shifted. Because of their lower chlorophyll content, norflurazon-treated plants were used to study the protochlorophyllide a photoreduction process triggered by one light flash. The first stable chlorophyllide photoproduct was a chlorophyllide a form emitting at 688 nm as in angiosperms. Further chlorophyllide a shifts usually observed in angiosperms were not detected. The rapid regeneration of photoactive protochlorophyllide a from nonphotoactive protochlorophyllide after one flash was demonstrated.